2008
DOI: 10.1007/s11240-008-9404-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of highly efficient genetic transformation protocols for table grape Sugraone and Crimson Seedless at low Agrobacterium density

Abstract: Highly efficient genetic transformation protocols and the regeneration of transgenic plants of Sugraone and Crimson Seedless grapevines (Vitis vinifera L.) were achieved from embryogenic calli co-cultured with low Agrobacterium tumefaciens densities. The sensitivity of embryogenic cultures to kanamycin, as well as the effect of Agrobacterium strains, C58(pMP90) or EHA105, and the bacterial concentration (0.06 or 0.2 at Optical Density OD 600 ) on transformation efficiency were studied. Embryogenic cultures sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In our experiments, both EHA105 and C58 could be used for transformation, but EHA105 seems to be better than C58, which is a hypervirulent bacterium that has been used successfully in the transformation of various plant species (Holland et al 1997;Li et al 2007a, b;López-Pérez et al 2008;Akcay et al 2009). …”
Section: Discussionmentioning
confidence: 75%
“…In our experiments, both EHA105 and C58 could be used for transformation, but EHA105 seems to be better than C58, which is a hypervirulent bacterium that has been used successfully in the transformation of various plant species (Holland et al 1997;Li et al 2007a, b;López-Pérez et al 2008;Akcay et al 2009). …”
Section: Discussionmentioning
confidence: 75%
“…Simple integration pattern was found in four of the five lines tested. Different authors [7,27,29,39] have reported variable insertion numbers ranging from 1 to 3 in genomic blottings with different gene probes in other cultivars of transformed grapevine via Agrobacterium. In our study a high proportion of a unique number of gene insertions in the transgenic cv.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a debate going on in the scientific press, about the risks of using the CaMV35S promoter regarding its "unpredictable" recombinogenic potential [13]. Constitutive promoters, such as CaMV35S, are typically used for grapevine transformation [15,29,30,39,42]. In order to avoid such problems, the use of tissue-specific promoters is an attractive alternative since gene expression is restricted to tissues of interest and at given developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…Agrobacterium tumefaciens EHA105-pKSTS706 at OD 600 = 0.2 were co-cultured with embryogenic calli for 2 days following the plant regeneration protocol described by López-Pérez et al (2008) and Dabauza and Velasco (2012): calli were washed with MS ? 900 mg l -1 cefotaxime for 20 min and cultured on MSAC [modified MS (half strength of macroelements MS), 100 mg l -1 myoinositol, 30 g l -1 sucrose and 2.5 g l -1 of activated charcoal (AC)] (López-Pérez et al 2005, 2006 with 300 mg l -1 cefotaxime for embryo differentiation.…”
Section: Genetic Transformation and Plant Regenerationmentioning
confidence: 99%